PENGARUH TEKANAN (PRESSURE), KESEMPATAN (OPPORTUNITY), RASIONALISASI (RATIONALIZATION), DAN KAPABILITAS (CAPABILITY) TERHADAP KECURANGAN PENGADAAN BARANG/JASA DI PEMERINTAHAN ACEH DENGAN PEMODERASI BUDAYA ETIS ORGANISASI - Fitri, finalia; Nadirsyah, Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study has purposes to discover whether pressure, opportunity, rationalization and capability influences towards fraud of procurement goods and services in Aceh Government with ethic cultural organization as a moderator. Testing was conducted to 20 SKPD in Aceh Government which arranged an event of procurement goods and services. This study uses primary data of questioner which was distributed to all 60 respondents that consist of Head of minister, Firma, Institute, Secretary, and Head of finance, the sample of study is taken by purposive sampling. Testing is conducted by using moderated analyzing Regression (MRA). The result of study shows that partially pressure and capability influences towards fraud of procurements good and service, meanwhile opportunity, rationalization, and ethic cultural organization were not influenced towards fraud of procurements goods and services. In testing of moderate regression analyzing uses interaction test, partially ethic cultural organize is able to moderate the relationship between opportunity and rationalization towards fraud of procurement. But, ethic cultural organization is not able to moderate the relationship between pressure and capability towards fraud of procurement goods and services.